Ferromagnetic–Antiferromagnetic Coupling by Distortion of Fe/Mn Oxygen Octahedrons in (BiFeO3)m(La0.7Sr0.3MnO3)n Superlattices. Issue 18 (10th March 2017) - Xiong, Jie; Lei, Tianyu; Chu, Junwei; Yang, Chao; Wei, Jiake; Zhuo, Mujin; Choi, Eun‐Mi; Tao, Bowan; Zhang, Wanli; Wang, Yongqiang; Li, Yanrong
Abstract : Interface enhanced magnetism attracts much attention due to its potential use in exploring novel structure devices. Nevertheless, the magnetic behavior at interfaces has not been quantitatively determined. In this study, abnormal magnetic moment reduction is observed in La0.7 Sr0.3 MnO3 (LSMO)/BiFeO3 (BFO) superlattices, which is induced by ferromagnetic (FM)/antiferromagnetic (AFM) coupling in the interface. With reduced repetition of the superlattice's unit cell [(LSMO) n /(BFO) n ]60/ n ( n = 1, 2, 5, 10) on a SrTiO3 substrate, magnetic moment reduction from 25.5 emu cc −1 ([(LSMO)10 /(BFO)10 ]6 ) to 1.5 emu cc −1 ([(LSMO)1 /(BFO)1 ]60 ) is obtained. Ab initio simulations show that due to the different magnetic domain formation energies, the magnetic moment orientation tends to be paramagnetic in the FM/AFM interface. The work focuses on the magnetic domain formation energy and provides a pathway to construct artificial heterostructures that can be an effective way to tune the magnetic moment orientation and control the magnetization of ultrathin films. Abstract : The ferromagnetic (FM)/antiferromagnetic (AFM) coupling between La0.7 Sr0.3 MnO3 (LSMO) and BiFeO3 (BFO) in [(LSMO) n /(BFO) n ]60/ n ( n = 1, 2, 5, 10) superlattices on SrTiO3 substrate is investigated. The work indicates that the FM/AFM coupling in the BFO/LSMO interface is an obstacle for enhancing the magnetic properties of BFO.